Confirmation bias in acquisition of information based on political affiliation - Silva, Marta Vasconcelos Barreto Resina da (2020)
This paper studies the impact of confirmation bias on the choice between biased sources of political information in a pre-election period. A sample of 204 Portuguese respondents was used, through a survey regarding their political identity and relating it to each one’s choice of information sources, as a voter and as a single decision-maker. Significant differences in behaviour were found according to one’s political identity. Evidence was found for some significant confirmation-seeking behaviour among right-wing participants, but some hypotheses concerning expressive voting and the effects of various factors on confirmation bias weren’t confirmed.